HOW CORPORATE GOVERNANCE IMPACTS TAX MANAGEMENT: A CLOSER LOOK - Evy Steelyana Wiyarti (Jurusan Akuntansi FEB UHO, 2024)
This research aims to examine the influence of profitability, the number of commissioners, and directors on tax management of property and real estate companies listed on the Indonesia Stock Exchange for the years 2017 – 2020. The method used is The research method used in this study is primarily an Inferential Statistical Analysis, supplemented by Descriptive Statistical Analysis for preliminary data exploration. Comparing the minimum, maximum, and average values between Commissioners and Directors. This research indicates that the Number of Commissioners, the Percentage of Independent Commissioners, and the Compensation of Commissioners and Directors significantly affect tax management. Good corporate governance can support tax management and enhance compliance with tax regulations. Due to inconsistent research findings and the current significance of tax savings as an interesting case to study.